Can sustainable health behaviour contribute to ensure healthy lives and wellbeing for all at all ages (SDG 3)? A viewpoint - Gloria Macassa (SAGE Publishing, 2021)
Sustainable health behaviours and, specifically, eating a sustainable diet and engaging in regular physical activity are health-promoting behaviours that can simultaneously contribute to reduction of greenhouse gases which are known to contribute to climate change. Good health usually facilitates societal development, and development often promotes improved health. However, while good health may be a prerequisite for societal development, some behavioural determinants of health, such as attitudes towards the environment, and people's lifestyles and consumption patterns, can impede the sustainability of the development process in the longer term. This perspective paper argues that there is a need to rethink 21st century health promotion practices by pairing sustainability literacy with health promotion for changing dietary and physical activity behaviour patterns to improve population health and contribute to the achievement of Sustainable Development Goal 3 (to ensure healthy lives and promote wellbeing for all at all ages).